Pemanfaatan Internet sebagai Sumber Belajar untuk Meningkatkan Prestasi Akademik Mahasiswa (Studi Kasus pada Mahasiswa Jurusan P.IPS FTIK UIN Maliki Malang) - Salem, Muh. Amiruddin; Arkiang, Fajeri (REMIK: Riset dan E-Jurnal Manajemen Informatika Komputer, 2020)
Abstract : The purpose of this research is to search the utilization of internet as learning resource media to improve student academic achievement. This research used descriptive method and qualitative method. The subject of this research is 4 students of social studies education of UIN Maliki Malang. The result of this research is the utilization of internet in among students of social studies education UIN Maliki Malang are as media of searching information to complete lecture assignments and to help students to find the creative new idea in the learning process and to support lectures to be more effective. As for the supporting factors in utilizing the Internet as a medium of learning resources by students is a willingness of high students in seeking knowledge from the various sources that they open through Internet sites and able to motivate students In utilizing it as a learning resource. While the inhibiting factor in utilizing the Internet as a source of learning is the dependence of students on the Internet, utilizing the Internet as entertainment media as well as slow Internet access so that students take a long time to access data. Keywords : Internet, Learning Resource, Academic Achievement